Effective Model-Based Systems Engineering - Borky, John M.; Bradley, Thomas H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This textbook presents a proven, mature Model-Based Systems Engineering (MBSE) methodology that has delivered success in a wide range of system and enterprise programs. The authors introduce MBSE as the state of the practice in the vital Systems Engineering discipline that manages complexity and integrates technologies and design approaches to achieve effective, affordable, and balanced system solutions to the needs of a customer organization and its personnel. The book begins with a summary of the background and nature of MBSE. It summarizes the theory behind Object-Oriented Design applied to complex system architectures. It then walks through the phases of the MBSE methodology, using system examples to illustrate key points. Subsequent chapters broaden the application of MBSE in Service-Oriented Architectures (SOA), real-time systems, cybersecurity, networked enterprises, system simulations, and prototyping. The vital subject of system and architecture governance completes the discussion. The book features exercises at the end of each chapter intended to help readers/students focus on key points, as well as extensive appendices that furnish additional detail in particular areas. The self-contained text is ideal for students in a range of courses in systems architecture and MBSE as well as for practitioners seeking a highly practical presentation of MBSE principles and techniques. Maximizes student understanding of MBSE with a realistic and feasible approach without excessive treatment of modeling theory; Emphasizes system architecture and engineering, including hardware, software, controlled equipment, networking, and other system elements, in contrast to the many existing books that focus largely or entirely on software; Reinforces concepts with end of chapter problems; Demonstrates how to model and manage both functional requirements and non-functional requirements that define overarching system characteristics such as openness, security, affordability, and ease of use; Provides a comprehensive introduction to all important areas of modern Systems Engineering practice, including the Model-Based System Architecture Process (MBSAP), Service-Oriented Architecture (SOA), real-time systems, cybersecurity, and networked enterprises; Illustrates every aspect of the methodology with detailed system examples.
Introduction - Framing the Problem -- Applying Object Orientation to System Architecture -- MBSAP Methodology Overview -- Analyzing Requirements in an Operational Viewpoint -- Designing in a Logical/Functional Viewpoint -- Implementing in a Physical Viewpoint -- Implementing Service-Oriented Architectures for Enterprise Integration -- Extending Architecture to Real-Time Domains -- Developing the Network Dimension -- Protecting Information with Cybersecurity -- Using Prototypes Verification, and Validation to Evaluate and Enhance System Architecture -- Using Reference Architectures and Frameworks -- Architecting the Enterprise -- Applying Advanced Concepts -- Implementing Governance to Measure and Maintain Architecture Quality -- Appendix A - Quick Reference to Object-Oriented Design (OOD) and the Unified Modeling Language (UML) -- Appendix B - Quick Reference to the System Modeling Language (SysML), Profile of the Unified Modeling Language (UML) -- Appendix C -- System Architecture Example: E-X AirborneMultisensor Platform -- Appendix D - Summary of the Modeling and Analysis of Real-Time and Embedded (MARTE) Systems Profile of UML -- Appendix E - Listing of Information Technology (IT) Core Standards and Sources -- Appendix F - Defense in Depth (DiD) Defintions -- Appendix G - Common Cyber Attack Methods -- Appendix H - IEEE Computer Society Center for Secure Design (SD) List of Top 10 Security Flaws -- Appendix I - Software Testing Methods and Tools -- Appendix J - Open System Interconnect (OSI) Layers and Protocols -- Appendix K - Service-Oriented Architecture (SOA) Policy Requirements for Department of Defense (DoD) Programs.
Keywords: Dynamics; Nonlinear theories; System theory; Control theory; Computer simulation; Applied Dynamical Systems; Systems Theory, Control; Computer Modelling; Complex Systems